Enhancing Chatbot Service User Satisfaction - Triyuth Promsiri; Naruemol Wuittipappinyo; Vasu Keerativutisest (My University, 2025)
Chatbots play an essential role in enhancing automated customer support experiences, with the global chatbot market estimated to reach $142 billion in 2024. Despite this growth, limited research addresses the factors influencing user satisfaction with chatbot services. Drawing from the literature on service and information quality, this study investigates how these factors impact chatbot service user satisfaction (CSUS). It hypothesizes that service quality (SQ) and information quality (IQ) are significant predictors of CSUS and that demographic variables like age may influence satisfaction levels. A survey of 385 Thai chatbot users were surveyed concerning their online service opinions, from which the data were analyzed using ANOVA and multiple regression. Results confirmed that both SQ and IQ significantly enhance CSUS. Additionally, age was a significant factor, with younger users (21-30 years) reporting higher satisfaction than older groups. These findings highlight the importance of delivering timely, accurate, and reliable information while ensuring visually appealing and user-friendly chatbot designs. The study underscores the need for businesses to adapt chatbot communication strategies to demographic preferences and to prioritize continuous updates and personalization. Future research should explore other potential influences, such as chatbot personality traits, perceived benefits, and cultural variations.
Keywords: Chatbot; User Satisfaction; AI in Service Interactions